Online Counseling: Advantages, Disadvantages and Ethical Issues - Kiriakaki, Sofia; Tzovanou, Maria; Sotiriou, Anastasia; Lampou, Maria; Varsamidou, Eleni (Homo Virtualis, 2022)
The present research aims to study some aspects of online counseling. More specifically, the possibilities, the difficulties, the effectiveness, as well as issues of ethics, which are raised through the internet practice, are being explored in the light of the mental health specialists that provide it. In addition, it is being examined the way in which covid-19 pandemic affected its demand. In order to conduct the research, a questionnaire was completed by 25 Greek experts who provide online counseling services. Then, their answers were quantified and compared with the data of the existing bibliography. The findings are in accordance with it on pros, cons, demand during the pandemic, and the effectiveness of online counseling compared to the in person one. However, a differentiation was observed, concerning the most prevailing way of conducting online counseling and the counselors’ perception of protection of their personal data. Restrictions such as the type of the sampling and the online giving of the questionnaire could affect the results of the research. Future studies could lead to further conclusions, by taking into account the findings and the limitations.